(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the role of various catalysts used in the production of furfural, as well as the influence of temperature, pressure and time on the production of furfural, and provides comparative data on polymer putties FAM, 2FAM, 3FAM.